Role of Perioperative Pregabalin in the Management of Acute and Chronic Post-Thoracotomy Pain - Gaber, Sara (Open Access Maced J Med Sci, 2019)
BACKGROUND: Post-thoracotomy pain syndrome (PTPS) can be challenging to treat. AIM: This study aimed to evaluate the efficacy of perioperative pregabalin in the prevention of acute and chronic post-thoracotomy pain. METHODS: Sixty patients scheduled for thoracotomy for oncologic surgeries were randomly allocated to one of two groups; Pregabalin and Control. In the Pregabalin group, pregabalin 150 mg was administered one hour before thoracotomy and 12 hours later, then every 12 hours for five days. Pain intensity was assessed using the Visual Analogue Scale (VAS) at rest (VAS-R) and dynamic (VAS-D) in the ICU and during the next four days. Morphine consumption and the frequency of side effects were recorded. Assessment of PTPS was done using the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) scale at 1, 2, and 3 months. RESULTS: The VAS-R and VAS-D scores and the total morphine consumption were significantly lower in Pregabalin group during days 0 through 4. Neuropathic pain, allodynia, and hyperalgesia were significantly lower in Pregabalin group after 1, 2, and 3 months. CONCLUSION: Pregabalin is effective in the reduction of chronic neuropathic pain at 1, 2, and 3 months after thoracotomy and it also reduces pain and opioid consumption during the acute postoperative period with few adverse effects.